Species on the move around the Australian coastline: A continental‐scale review of climate‐driven species redistribution in marine systems. (7th May 2021) - Gervais, Connor R.; Champion, Curtis; Pecl, Gretta T.
Abstract: Climate‐driven changes in the distribution of species are a pervasive and accelerating impact of climate change, and despite increasing research effort in this rapidly emerging field, much remains unknown or poorly understood. We lack a holistic understanding of patterns and processes at local, regional and global scales, with detailed explorations of range shifts in the southern hemisphere particularly under‐represented. Australian waters encompass the world's third largest marine jurisdiction, extending from tropical to sub‐Antarctic climate zones, and have waters warming at rates twice the global average in the north and two to four times in the south. Here, we report the results of a multi‐taxon continent‐wide review describing observed and predicted species redistribution around the Australian coastline, and highlight critical gaps in knowledge impeding our understanding of, and response to, these considerable changes. Since range shifts were first reported in the region in 2003, 198 species from nine Phyla have been documented shifting their distribution, 87.3% of which are shifting poleward. However, there is little standardization of methods or metrics reported in observed or predicted shifts, and both are hindered by a lack of baseline data. Our results demonstrate the importance of historical data sets and underwater visual surveys, and also highlight that approximately one‐fifth of studies incorporated citizen science. These findings emphasize the important role the public has had, and can continue to play, in understanding the impact of climate change. Most documented shifts are of coastal fish species in sub‐tropical and temperate systems, while tropical systems in general were poorly explored. Moreover, most distributional changes are only described at the poleward boundary, with few studies considering changes at the warmer, equatorward range limit. Through identifying knowledge gaps and research limitations, this review highlights future opportunities for strategic research effort to improve the representation of Australian marine species and systems in climate‐impact research. Abstract : With the continued rise in sea surface temperature, species redistributions are becoming more commonplace around the world. Around Australia, at least 198 marine species, from 9 phyla, are redistributing their distributions, 87% of which are shifting poleward, in accordance with climate change. ​